CHARACTER EDUCATION IN THE QUR'AN; PATIENCE, HONESTY AND RESPONSIBILITY - Nana Mulyana; Aceng Nurul Huda, Achmad Saefurridjal, Iskandar Mirza; Ajat Saputra (International Journal of Teaching and Learning, 2026)
This study aims to analyze character education in the Qur'an; patience, honesty and responsibility. This study uses a method with a qualitative approach. Observing the condition of the Indonesian nation which is on the verge of moral decay and quite threatening the continuity of national and state life, has encouraged the government to take the initiative to prioritize character development. National character development through character education is used as the main stream of national development. The results of this study can be concluded that character education based on the values of the Qur'an such as patience, honesty, and responsibility is very important to form individuals with noble morals. By applying these values in everyday life, it is hoped that the younger generation can grow into good individuals, useful for themselves, their families, and society.